Analisis manajemen risiko teknologi digital dalam layanan m-banking pada bank syariah: studi literatur: Studi Literatur - Anggraeni, Novita Putri (Maliki Interdisciplinary Journal, 2025)
The growth of mobile banking services in Islamic banking has brought transactional convenience but also introduced digital risks such as cybercrime, data breaches, and human error. This study aims to analyze the implementation of risk management in facing these digital challenges through a literature review of various scholarly sources, journals, and relevant articles. The findings reveal that effective risk management comprising identification, assessment, control, and monitoring is essential to maintain the resilience and credibility of Islamic banks. Compliance with OJK regulations and IFSB standards also plays a critical role in ensuring that Sharia principles align with technological advancement. Additionally, customer education and improved digital literacy serve as significant supporting strategies. This study is expected to contribute to the development of more structured and systematic digital risk management strategies to establish secure, reliable, and sustainable Islamic banking services in the digital era.